2020
DOI: 10.1016/j.ijleo.2019.163222
|View full text |Cite
|
Sign up to set email alerts
|

Study on isolation and radiation behaviours of a 34×34 array-antennas based on SIW and metasurface properties for applications in terahertz band over 125–300 GHz

Abstract: This paper describes the feasibility of conceptual design of a 34×34 array antenna for operation at Terahertz over a frequency range of 125-300 GHz for S11≤-10dB, which corresponds a fractional bandwidth of 82.35%. Each radiation element constituting the array consists of a square patch of dimensions of 2×2 mm 2 that are excited by a matched microstrip line. Each patch is isolated from each other with metallic via-holes, which are implemented based on the substrate integrated waveguide (SIW) technique. This te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…In [133], the possibility of a perceptual model of a 34×34 array antenna for working throughout 0.125 to 0.3 THz, which relates to a feasible bandwidth of 82.35% is described. Fig.19 shows that, each of the radiation elements which constitute the array comprises of a square patch having a physical dimension of 2 × 2 mm 2 and stimulated via a matched microstrip line.…”
Section: Study On Interferences Reduction and Radiation Behavioursmentioning
confidence: 99%
“…In [133], the possibility of a perceptual model of a 34×34 array antenna for working throughout 0.125 to 0.3 THz, which relates to a feasible bandwidth of 82.35% is described. Fig.19 shows that, each of the radiation elements which constitute the array comprises of a square patch having a physical dimension of 2 × 2 mm 2 and stimulated via a matched microstrip line.…”
Section: Study On Interferences Reduction and Radiation Behavioursmentioning
confidence: 99%
“…It has been shown that mutual coupling among neighboring radiating elements in the antenna can be improved by increasing the space between the elements, but this is at the cost of increased antenna size [20]. Many techniques have been investigated to reduce mutual coupling between elements, which include using metamaterials [21][22][23][24][25], metasurface [26][27][28], and embedded periphery slot [29].…”
Section: Introductionmentioning
confidence: 99%
“…In [19,20], an antenna array consisting of patches that were combined in series and/or in parallel arrangements to provide high directivity was introduced. Several papers have been introduced to address the problems of mutual coupling between elements and the radar cross section of the antenna array, as well as to provide high isolation between elements [21][22][23][24]. Vasanelli et al [23] introduced a low radar cross-section antenna array based on the use of an artificial magnetic conductor (AMC) that was set around the series antenna to reduce the reflection in the direction of car fascia.…”
mentioning
confidence: 99%
“…The AMC had the capability to eliminate reflected waves from the antenna. Furthermore, in the last few months, Alibakhshikenari et al used metamaterial unit cells [21] and metasurfaces [22,24] to reduce the mutual coupling between antenna elements to be compatible for radar applications.Most of the radars in this side use two transmitters with two unique radiation patterns to give the long-range radar (LRR) and medium-range radar (MRR) modes. However, the performance of this system is not efficient for automotive radar due to the switching performance (time response and losses) between the two modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation